2018
DOI: 10.1177/000313481808400225
|View full text |Cite
|
Sign up to set email alerts
|

Head CT before Transfer Does Not Decrease Time to Craniotomy for TBI Patients

Abstract: Rural trauma education emphasizes that radiologic imaging should be discouraged if it delays transfer to definitive care. With increased capacity for image sharing, however, radiography obtained at referring hospitals (RH) could help providers at trauma centers (TC) prepare for patients with traumatic brain injury. We evaluated whether a head CT prior to transfer accelerated time to neurosurgical intervention at the TC. The study was conducted at a combined adult Level I and pediatric Level II TC with a catchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
0
7
0
Order By: Relevance
“… 13 Delays in acquiring the scan may lead to worse patient outcomes. 14 , 15 Although novel, portable, affordable technologies are being trialed for low-resource settings (e.g., handheld near-infrared spectroscopy devices for traumatic intracranial hematomas), CT scans remain the gold standard for rapid and accurate head imaging in neurotrauma. Multiple studies have also shown that the advent of CT imaging reduces mortality in the setting of central nervous system infections, which are more frequent in lower-income settings.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Delays in acquiring the scan may lead to worse patient outcomes. 14 , 15 Although novel, portable, affordable technologies are being trialed for low-resource settings (e.g., handheld near-infrared spectroscopy devices for traumatic intracranial hematomas), CT scans remain the gold standard for rapid and accurate head imaging in neurotrauma. Multiple studies have also shown that the advent of CT imaging reduces mortality in the setting of central nervous system infections, which are more frequent in lower-income settings.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of pretransfer CT on increased transfer time has also been observed in a U.S. study in patients with head injuries 35 . In addition, a 2022 study showed significant variation in ED length of stay between referring hospitals, which may have been partly driven by unnecessary CTs 36 .…”
Section: Discussionmentioning
confidence: 70%
“…Glasgow coma score (GCS) as an independent factor was mixed among studies; for many, a “lower GCS” was associated with an increased likelihood of repeat scan. However, there was no agreement on a cutoff value, and for multiple studies GCS was not found to be a statistically significant independent risk factor for repeat [ 5 , 10 , 26 , 30 , 38 - 40 ]. Factors that were not significant predictors were patient race and the status of Advanced Trauma Life Support (ATLS) certification of the ordering physician [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there exists data to suggest that even for patients with severe traumatic brain injury (TBI), CTH at referring institutions does not decrease time to neurosurgical intervention at the receiving trauma center [ 40 ]. On the contrary, a 2018 retrospective study at a level I trauma center in Iowa found the elapsed time between arrival at OSH and the start of the neurosurgical procedure for those who received OSH scan versus those who didn’t was an average of 5 hours, 6 minutes and 3 hours, 9 minutes, respectively [ 40 ]. One contributing factor was that more than 25% of those who were imaged at the OSH were reimaged at the trauma center.…”
Section: Discussionmentioning
confidence: 99%